Estrategia didáctica de mobile learning para la enseñanza en la asignatura devenir y movimiento - Salgado, José Orlando (Universidad Antonio Nariño, 2023)
The theme of study of this project is part of university education, and deals with of the thematic relationship of the body in movement, included in the subject Becoming and Movement, subject taught in the fourth semester of the Plastic and Visual Arts career. This relationship is established as a form of representation, from the Paleolithic, drawing a line of very extensive time, going through various periods and coming to present various artistic manifestations, included in current art; It is notorious that in some of these At times art and artists are not interested in this relationship, or it does not appear so explicit, and what that is found as a theme is the counterpart, that is to say frozen body and movement.